A reverse J-shaped association between adherence to planetary health diet and all-cause and cause-specific mortality in Japan: a cross-sectional prefecture-level ecological study - Daiki Watanabe; Yumiko Inoue (Journal of Nutritional Science)
Epidemiological studies have reported an association between the planetary health diet (PHD), diet-related greenhouse gas emissions (GHGEs), and mortality. However, data from individuals from non-Western countries was limited. Therefore, we aimed to examine this association among Japanese individuals using a cross-sectional ecological study of all 47 prefectures in Japan. Prefecture-level data were obtained from government surveys. The dietary amount was estimated based on the weight of food purchased (211 items) from the 2021–2023 Family Income and Expenditure Survey. Adherence to PHD was scored using the EAT-Lancet index (range, 0 [worst] to 42 [best]) and categorised into four groups: ≤ 24 (n = 14, low), 25 (n = 17, medium-low), 26 (n = 10, medium-high), and 27 points (n = 6, high). Diet-related GHGEs were estimated using previously developed GHGE tables for each food item. Mortality data were obtained using the 2022 Vital Statistics. Mortality rate ratio (RR) was calculated using a multivariate Poisson regression model. After adjusting for confounders, compared to the prefecture in the medium-low group of adherence score, those in the low and high groups were associated with a higher mortality RR for all-cause (low group: RR = 1.03 [95% CI (confidence interval) = 1.01–1.05]; high group: RR = 1.03 [95% CI = 1.00–1.07]) and pneumonia. Moreover, although a higher adherence score was inversely associated with GHGE, it was linked to an increased mortality risk from heart disease and stroke. Our findings indicate a reverse J-shaped association between adherence to PHD and mortality.